Cultural diversity, geographical isolation, and the origin of the wealth of nations - Quamrul Ashraf; Oded Galor (Institute for the Study of Labor (IZA), 2012)
This research argues that variations in the interplay between cultural assimilation and cultural diffusion have played a significant role in giving rise to differential patterns of economic development across the globe. Societies that were geographically less vulnerable to cultural diffusion benefited from enhanced assimilation, lower cultural diversity, and more intense accumulation of society-specific human capital. Thus, they operated more efficiently with respect to their production-possibility frontiers and flourished in the technological paradigm that characterized the agricultural stage of development. The lack of cultural diffusion and its manifestation in cultural rigidity, however, diminished the ability of these societies to adapt to a new technological paradigm, which delayed their industrialization and, hence, their take-off to a state of sustained economic growth. The theory thus contributes to the understanding of the advent of divergence and overtaking in the process of development. Consistently with the theory, the empirical analysis establishes that (i) geographical isolation prevalent in pre-industrial times (i.e., prior to the advent of airborne transportation technology) has had a persistent negative impact on the extent of contemporary cultural diversity; (ii) pre-industrial geographical isolation had a positive impact on economic development in the agricultural stage but has had a negative impact on income per capita in the course of industrialization; and (iii) cultural diversity, as determined exogenously by pre-industrial geographical isolation, has had a positive impact on economic development in the process of industrialization.
urn:nbn:de:101:1-2012042310329
Keywords: O11; O13; O14; O31; O33; O41; O43; O50; 330; cultural assimilation; cultural diffusion; cultural diversity; geographical isolation; economic development; agriculture; industrialization; Gesellschaft; Kulturelle Identität; Soziale Beziehungen; Pluralismus; Geographie; Landwirtschaft; Industrialisierung; Entwicklung; Wirtschaftssoziologie; Sozialgeschichte